2011
DOI: 10.1007/s10750-011-0694-4
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire induced changes in aquatic invertebrate communities and mercury bioaccumulation in the Okefenokee Swamp

Abstract: Fire is an important natural disturbance in the Okefenokee Swamp. From April-June 2007, wildfire burned 75% of the wetland area. With the existence of extensive pre-fire data sets on community structure and total mercury of invertebrates, the fire presented an opportunity to assess impacts of wildfire on invertebrates. Post-fire collection of samples occurred in September, December, and May, 2007-2009. Sample sites included 13 burned and 8 non-burned (reference) sites. Comparisons of data among pre-fire, post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Moreover, indirect impacts linked to habitat and trophic alterations of the community were also detected, similar to other lentic systems affected by wildfire (Beganyi & Batzer, 2011;de Szalay & Resh, 1997;Lewis et al, 2014). Moreover, indirect impacts linked to habitat and trophic alterations of the community were also detected, similar to other lentic systems affected by wildfire (Beganyi & Batzer, 2011;de Szalay & Resh, 1997;Lewis et al, 2014).…”
Section: Seasonal Trends and Community Recoverysupporting
confidence: 61%
See 2 more Smart Citations
“…Moreover, indirect impacts linked to habitat and trophic alterations of the community were also detected, similar to other lentic systems affected by wildfire (Beganyi & Batzer, 2011;de Szalay & Resh, 1997;Lewis et al, 2014). Moreover, indirect impacts linked to habitat and trophic alterations of the community were also detected, similar to other lentic systems affected by wildfire (Beganyi & Batzer, 2011;de Szalay & Resh, 1997;Lewis et al, 2014).…”
Section: Seasonal Trends and Community Recoverysupporting
confidence: 61%
“…As predicted, in Mediterranean temporary ponds, the direct effects of wildfire played a major role compared to perennial aquatic ecosystems. Moreover, indirect impacts linked to habitat and trophic alterations of the community were also detected, similar to other lentic systems affected by wildfire (Beganyi & Batzer, 2011;de Szalay & Resh, 1997;Lewis et al, 2014). Therefore, intermittency adds a new path of disturbance for the aquatic community: a decrease in the abundance of organisms resting in sediments during the dry phase, probably directly burned by the wildfire.…”
Section: Seasonal Trends and Community Recoverysupporting
confidence: 61%
See 1 more Smart Citation
“…have addressed how river catchments respond to prescribed vegetation burning (e.g., Britton 1991, Bêche et al 2005, Arkle and Pilliod 2010 in comparison to wildfires, which have received much more attention (e.g., Dwire and Kauffman 2003, Minshall 2003, Beganyi and Batzer 2011, Verkaik et al 2013.…”
mentioning
confidence: 99%
“…Minshall (2003) suggested that intense fires will have larger effects on stream fauna, which has been corroborated by findings following an intense fire in California (Oliver et al 2012) and another in central Victoria, Australia (Verkaik et al 2014). In contrast, some authors suggest that wetland invertebrates cope well with a variety of stresses (Beganyi and Batzer 2011) and may show little response to fire compared to stream communities (Minshall 2003). Our findings support this conclusion for G. falcata, which typically occurs in seasonal wetland and flooded vegetation habitats and appeared to be least affected by fire.…”
Section: Wildfire and Droughtmentioning
confidence: 92%